2022
DOI: 10.1101/2022.03.24.22272837
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differences in transcriptional response underlie why prior vaccination exceeds prior infection in eliciting robust immune responses in Omicron infected outpatients

Abstract: The antibody response following Omicron infection has been reported to be less robust than to other variants. Here we compared the immune-transcriptome and antibody responses following Omicron infection in unvaccinated and vaccinated individuals who experienced mild to moderate symptoms. The unvaccinated individuals showed a quantitatively greater transcriptional response but a muted antibody response than vaccinated individuals. Prior vaccination modifies the transcriptional response to Omicron infection with… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…While the Omicron BA.1 and BA.2 sublineages share mutations they also carry unique mutations, 28 in BA.2, which can explain their differential response to vaccine-induced and therapeutic antibodies (Ai et al, 2022; Arora et al, 2022a; Arora et al, 2022b). Previous studies have also demonstrated that BA.1 infection of naïve persons yields a very limited antibody response to SARS-CoV-2 VOCs other than Omicron itself (Lee et al ., 2022b; Rössler et al, 2022). However, prior vaccination or prior infection with older SARS-CoV-2 variants augment the immune response upon BA.1 breakthrough infection (Lee et al ., 2022b; Rössler et al ., 2022).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…While the Omicron BA.1 and BA.2 sublineages share mutations they also carry unique mutations, 28 in BA.2, which can explain their differential response to vaccine-induced and therapeutic antibodies (Ai et al, 2022; Arora et al, 2022a; Arora et al, 2022b). Previous studies have also demonstrated that BA.1 infection of naïve persons yields a very limited antibody response to SARS-CoV-2 VOCs other than Omicron itself (Lee et al ., 2022b; Rössler et al, 2022). However, prior vaccination or prior infection with older SARS-CoV-2 variants augment the immune response upon BA.1 breakthrough infection (Lee et al ., 2022b; Rössler et al ., 2022).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have also demonstrated that BA.1 infection of naïve persons yields a very limited antibody response to SARS-CoV-2 VOCs other than Omicron itself (Lee et al, 2022b;Rössler et al, 2022). However, prior vaccination or prior infection with older SARS-CoV-2 variants augment the immune response upon BA.1 breakthrough infection (Lee et al, 2022b;Rössler et al, 2022). Our study now reveals that in antigen naïve individuals the immunologic response following BA.2 infection is even lower than that elicited by BA.1 infection as indicated by significantly lower antibody titers against all VOCs.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations